Sustainable solutions for organic waste management - Kuzmin, K. S. (ТДАТУ, 2021)
Waste disposal problem is relevant due to the trend towards the agglomeration enlargement, concentration of most of the population in cities and accumulation of various types of waste at dumps. Different types of organic and inorganic waste products require colossal energy costs for their recycling or disposal. Waste management may or may not include waste recycling - process of converting the physical, chemical or biological state of waste to provide subsequent waste management activities. Currently, the biological, thermal, chemical, mechanical and mixed methods of organic waste utilization are used.
Keywords: Waste disposal problem; recycling; disposal